HUBUNGAN PENGETAHUAN IBU TENTANG STIMULASI PERKEMBANGAN ANAK TERHADAP PERKEMBANGAN ANAK USIA PRASEKOLAH - Bratha, Shinta Dewi Kasih; Rosyadi, Imron (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
One of the stages of growth and development that children go through is the preschool age stage (age 4-5 years). The achievement of optimal growth and development depends on its biological potential. In order for a child to develop optimally, a constant and loving stimulation of the mother must be given. This study aims to look at the relationship of maternal knowledge about the stimulation of children's development to the development of preschool-age children. The design of this research is a cross-sectional study. Tools in data collection using questionnaires. The sample in the study was 44 mothers who had preschool-age children. The result of bivariate analysis obtained p-value 0,002. This means that there is a relationship between the level of knowledge of the mother and the development of preschool-age children.